Amino acid sequence data of alpha-tubulin from myxamoebae of Physarum polycephalum. - Singhofer-Wowra, M; Little, M; Clayton, L; Dawson, P; Gull, K (1986)
About 96% of the amino acid sequence of an alpha-tubulin from the slime mould Physarum polycephalum has been determined. Of 430 sequenced amino acids, 30 differ from the deduced amino acid sequence of a recently published alpha-tubulin complementary DNA from the plasmodial form of P. polycephalum. The myxamoebal alpha-tubulin differs from all other known alpha-tubulins in one of the last three C-terminal amino acids that are Gly-Glu-Tyr instead of the usual Glu-Glu-Tyr. These last three amino acids are preceded by 11 residues that appear to be particularly susceptible to mutation. No heterogeneity was found whilst sequencing the myxamoebal alpha-tubulin, indicating that only one type of alpha-tubulin is present in myxamoebae. This alpha-tubulin appears to be less conserved than the previously described plasmodial alpha-tubulin, supporting the hypothesis that the structural constraints on tubulin in axonemes have a significant effect on its rate of mutation.